Chromogenic Assay : A Critical Diagnostic Tool for Accurate Diagnosis of Severe Hemophilia A - Krishna, Goutham; Diljith, Hitha; Majeed, Abdul (Indian Journal of Child Health, 2024)
Haemophilia A is a genetic disorder characterized by the absence or reduced activity of factor VIII (FVIII), a crucial protein for blood clotting. The severity of Haemophilia A is directly related to the level of FVIII activity in the blood. The conventional one-stage clotting assay is the most commonly used diagnostic tool due to its simplicity and widespread availability. However, in cases of mild or moderate Haemophilia A, there can be significant disparities between results obtained from one-stage and two-stage assays. These discrepancies can result in normal FVIII levels being reported by the one-stage assay, potentially leading to a missed diagnosis or underestimation of the patient's bleeding risk. We present a case of a 18-year-old male diagnosed with severe Haemophilia A. The patient’s medical history included multiple severe bleeding episodes, including spontaneous haemarthrosis and prolonged bleeding following minor injuries. Despite these symptoms, the initial diagnostic approach using the one-stage assay suggested normal FVIII activity, which could have led to inadequate treatment and management strategies. Findings in Chromogenic Assay were crucial in correctly identifying the severe nature of the disorder, thus underscoring the importance of using multiple diagnostic tools to confirm FVIII activity levels. This case highlights the role of the chromogenic assay in the accurate diagnosis of Haemophilia A, particularly in patients where clinical symptoms do not match with one-stage assay results. This case emphasizes the need for heightened awareness among clinicians regarding the limitations of the one-stage assay and the benefits of incorporating the chromogenic assay into routine diagnostic practice for Haemophilia A.